PHYSICAL ACTIVITY, HEALTH CONDITION AND LIFESTYLE OF ACADEMIC YOUTH - Jakubowska, Luba; Grabowska, Barbara; Seń, Mariola (Journal of Education Culture and Society, 2019)
Introduction: Living in the age of modern inventions one forgets about one of the best medications for many health problems, which is physical activity. In 2016, Kantar Public (Ministry of Sport and Tourism, 2016) announced that only one in five Poles aged 15-69 had an adequate level of physical activity. A CBOS (Centre for Public Opinion Research) survey conducted in 2014 showed that half of Poles weigh too much. For the development of lifestyle diseases, besides overweight, the wrong lifestyle also contributes (CBOS No. 122/2014). According to the WOBASZ (a multi-center nationwide survey of the health status of the population) survey, only 3% of Polish society is characterized by "an indicator of a healthy lifestyle" (Kwaśniewska, Kaczmarczyk-Chałas, Dziankowska-Zaborszczyk, Kucharczyk, Drygas, 2010). The role and task of physical activity at an early age, as well as at any other stage of life, is very important in the prevention of civilization diseases, which is why it is crucial to monitor it. Aim of the study: The aim of the study was to assess the relationship between the level of physical activity, state of health and the lifestyle of the academic youth. Material and methods: The research was carried out among students from three universities in Wrocław (n = 629): University of Wrocław (UWr), Wrocław University of Science and Technology (PWr) and Wrocław Medical University (UM). The study used self-constructed questionnaires: physical activity questionnaire, health questionnaire, lifestyle questionnaire. The following statistical analyzes of the results were used: Shapiro-Wilk test, Pearson chi-square test independence, post-hoc test, analysis of variance (ANOVA), correlation coefficient rank (Spearman) and Pearson’s correlation coefficient. In the calculations, the package of computer programs STATISTICA v. 9.0 was used. Hypotheses verified at the level of p ≤0.05. Results: Health was the highest-rated one of the studied factors. In addition, it was found that as much as 67.7% of students from all universities represent a very good level of lifestyle. 68.4% of the respondents were characterized by a very good health potential. Research has shown that the physical activity of students from Medical University is at a higher level than students of PWr and UWr. Among the demographic variables, gender turned out to be important (men perform physical activity more often than women, while BMI and place of origin did not affect the physical activity of students). Studies have confirmed the relationship between all major variables (physical activity, lifestyle and health). The increase in the level of physical activity is accompanied by an increase in the level of lifestyle. A positive correlation between lifestyle factor and health condition was also observed.